A dopaminergic axon lattice in the striatum and its relationship with cortical and thalamic terminals. - Moss, J; Bolam, J (2008)
Interactions between glutamatergic corticostriatal afferents and dopaminergic nigrostriatal afferents are central to basal ganglia function. The thalamostriatal projection provides a glutamatergic innervation of similar magnitude to the corticostriatal projection. We tested the hypotheses that (1) thalamostriatal synapses have similar spatial relationships with dopaminergic axons as corticostriatal synapses do and (2) the spatial relationships between excitatory synapses and dopaminergic axons are selective associations. We examined at the electron microscopic level rat striatum immunolabeled to reveal vesicular glutamate transporters (VGluTs) 1 and 2, markers of corticostriatal and thalamostriatal terminals, respectively, together with tyrosine hydroxylase (TH) to reveal dopaminergic axons. Over 80% of VGluT-positive synapses were within 1 microm of a TH-positive axon and >40% were within 1 microm of a TH-positive synapse. Of structures postsynaptic to VGluT1- or VGluT2-positive terminals, 21 and 27%, respectively, were apposed by a TH-positive axon and about half of these made synaptic contact. When structures postsynaptic to VGluT-positive terminals and VGluT-positive terminals themselves were normalized for length of plasma membrane, the probability of them being apposed by, or in synaptic contact with, a TH-positive axon was similar to that of randomly selected structures. Extrapolation of the experimental data to more closely reflect the distribution in 3D reveals that all structures in the striatum are within approximately 1 microm of a TH-positive synapse. We conclude that (1) thalamostriatal synapses are in a position to be influenced by released dopamine to a similar degree as corticostriatal synapses are and (2) these associations arise from a nonselective dopaminergic axon lattice.